EKSTRAK ETER KULIT BUAH MANGGIS (Garcinia mangostana) TERHADAP LARVA NYAMUK Culex quinquefasciatus - , RR.INDAH PERMATA SARI; , Dra. Tri Murini, Msi, Apt ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: In recent, infection of lymphatic filariasis is a disease that is very common in Indonesia caused by Wucheria bancrofti. The main vector of filariasis is Culex quinquefasciatus . The main way to control the incidence of infectious disease lymphatic filariasis is to break the chain of the life cycle of the vector. Larvicidal natural and easy to find in the community for example is the pericarp of the mangosteen fruit (Garcinia mangostana L.) is used as a natural larvicidal. Objective: This study was made to determine the effect of the ether extract of mangosteen (Garcinia mangostana L.) pericarp against Culex quinquefasciatusâs larvae mortality . Methods: The study was performed using simple experimental study using WHO 2005 as the guide. Research for the initial test was performed to determine the range of 6 concentrations (2000 ppm, 4000 ppm, 8000 ppm, 11.000 ppm, 15.000 ppm, 18.000 ppm,) treatment performed 3 times at the end of the test using 10 larvae at each concentration in 100 ml. The final result is analyzed wih Probit and ANOVA. Results: LC50 is in 4626,964 ppm dosage of the extract and LC90 is in 16770,38 ppm. Conclusion:Ether extract of mangosteen (Garcinia mangostana L.) pericarp has a larvicidal against Culex quinquefasciatusâs larvae, but not effective.